Investor-State Arbitration Meets Mediation: Is Mediation the Future of Investor-State Dispute Settlement in Africa? - (:unkn) unknown (My University, 2020)
Many see the Pan-African Investment Code (PAIC), a model instrument adopted by the African Union (AU) in 2015, as the first step toward the ‘africanization’ of international investment law. While several national and regional instruments on foreign investments had been adopted by African States and Regional Economic Communities (RECs) prior to the PAIC, the latter’s unprecedented provisions and continental scope signaled a new level of integration with regard to the regulation of foreign investments in Africa. Among other innovative provisions – such as the inclusion of direct obligations on investors or the dismissal of equivocal protection standards such as Fair and Equitable Treatment –, the PAIC introduced alternative dispute resolution (ADR), including but not limited to mediation, as a mandatory step in solving investment disputes. Article 42 on Investor-State Dispute Settlement (ISDS) notably provides that ‘pursuant to this Code, the investor and the Member State should initially seek to resolve the dispute within six months at the latest, through consultations and negotiations, which may include the use of non-binding third-party mediation or other mechanisms’.Building on the PAIC, the African Continental Free Trade Area (AfCFTA) Protocol on Investment is soon to be published. For the reasons discussed below, the Protocol may very well further promote the use of mediation alongside or instead of arbitration in the resolution of investor-State disputes in Africa.
Keywords: African Research